Hedge fund of funds investing : an investor's guide - Nicholas, Joseph G., 1959- (Bloomberg professional library., 2004)
Hedge funds have rightly gained the attention of private and institutional investors in recent years, proving themselves as useful portfolio diversifiers and preservers of wealth while greatly dispelling their reputation as an "unsafe" investment. Yet investors attempting to navigate in the field of hedge funds face significant challenges: the large number of funds, the diversity of strategies used, the range of financial instruments traded, and the various formats for investing. Pooling multiple hedge funds together into one vehicle, the fund of funds provides a ready solution, combining professional management expertise with asset allocation. In this book--the first of its kind--industry expert Joseph Nicholas shows investors how these funds operate, the benefits and risks, and the criteria and due diligence to utilize when selecting funds. Nicholas provides an in-depth analysis of historical fund performance and offers unique insight into the industry and trends that may affect its evolution. Clear, insightful, and illustrated with numerous charts and graphs, Hedge Fund of Funds Investing is an essential resource for serious investors